Differences in Family Risk Factors of Drug Usage in Adolescent Girls and Boys - Radovanovic, Ivana D.; Maljković, Marija (NBP. Nauka, bezbednosti, policija, 2026)
Adolescence is a critical age for the onset of drug use, linked with many risk factors, among which are family factors. This study aimed to investigate 30 family risk factors of drug usage and subsequent gender differences between male and female adolescents. Data was collected from a representative sample of 1287 high school students (Mage = 17.04, SDage = 1.147) from Belgrade, Serbia, of which 52.5% were girls. Participants filled out an anonymous self-evaluation questionnaire during their school hours, with assistance from a school psychologist. Drug usage was defined through the use of cannabinoids, depressants, stimulants, or hallucinogens at least twice in the past. Family risk factors were reported by participants using a checklist listing 30 experiences identified in the literature as risk factors related to the family context. Canonical discriminant analysis was applied separately on the samples of boys and girls and two statistically significant discriminant functions were obtained. In the sample of boys, this function was defined by 7 family variables, 6 of which were predictors of differences between drug usage and non-usage. In the sample of girls, 13 factors influenced the differences between drug usage and non-usage. The only common risk factors in both boys and girls were frequent quarrels with parents, poor communication with family members, and adolescents’ attempts to run away from home. Discussed are the differences in the number and nature of family risk factors for drug use in boys and girls, as well as practical implications for drug use prevention programs.